Traumatic Brain Injury: Comparison of Computed Tomography Findings in Pediatric and Adult Populations - Madhur Choudhary; Khursheed Alam Khan; Nandkishore Gora; Achal Sharma; Virendra Deo Sinha (Indian Journal of Neurosurgery)
Introduction Traumatic brain injury (TBI) is a global health issue, accounting for a significant number of adult and pediatric deaths and morbidity. Computed tomography (CT) is an important diagnostic modality for TBI. The primary goal of this study was to determine if there were any significant radiological differences in CT brain findings between adult and pediatric populations. Materials and Methods Data of individual patients were collected from admission to discharge/death, which included various parameters in terms of demographics, mechanism of injury, and patient outcome which were later analyzed. A total of 1,150 TBI patients were enrolled in the study. Results The most common mode of injury in adults is road traffic accident (RTA) followed by fall from height (FFH), while in pediatrics it is vice versa. Findings of basal cisterns on CT brain were found to be statistically significant in both groups; 65% adults and 71% pediatrics had only one abnormal CT finding. Most common combination CT finding in adults was acute subdural hematoma (ASDH) and basal cistern abnormality, while in pediatrics it was traumatic subarachnoid hemorrhage (SAH) and contusion. Rotterdam score (based on CT brain findings) was significantly lower for pediatric age group compared with adults. It was 2.2 ± 0.85 for adults and 1.99 ± 0.74 for pediatrics, which was statistically significant (p < 0.001). Conclusions The Rotterdam score has immense predictive power for prognostication of mortality status. Pediatric age group has better prognosis in terms of survival as compared with adults, thus justifying the role of Rotterdam CT score for mortality risk stratification in providing clinical care.